2005
DOI: 10.1677/jme.1.01801
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, expression and characterization of three types of 17β-hydroxysteroid dehydrogenases from the Nile tilapia, Oreochromis niloticus

Abstract: In order to elucidate the roles of 17 -HSDs in fish gonadal steroidogenesis, three types of 17 -HSDs (17 -HSD1, 17 -HSD8 and putative 17 -HSD12) were cloned and characterized from the Nile tilapia, Oreochromis niloticus. The cloned cDNAs of 17 -HSD type 1, 8 and 12 were 1504, 1006 and 1930 bp long, with open reading frames encoding proteins of 289, 256 and 314 aminoacids, respectively. Tissue distribution pattern analyzed by RT-PCR and Northern blot showed that 17 -HSD1 was dominantly expressed in the ovary, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 36 publications
3
28
1
Order By: Relevance
“…5), while StAR mRNA was not quantifiable. Several studies have reported the expression of steroidogenic enzymes and proteins in fish hepatic tissues (von Hofsten et al 2002;Wang and Ge 2004;Zhou et al 2005). To our knowledge, our studies represent the first reports of the parallel expression of aromatase gene isoforms, StAR, CYP11β and 3β-HSD in fish liver and the subsequent modulation by an estrogen mimic (Mortensen and Arukwe 2007).…”
Section: Star and P450scc Expression In Non-steroidogenic Tissuessupporting
confidence: 49%
“…5), while StAR mRNA was not quantifiable. Several studies have reported the expression of steroidogenic enzymes and proteins in fish hepatic tissues (von Hofsten et al 2002;Wang and Ge 2004;Zhou et al 2005). To our knowledge, our studies represent the first reports of the parallel expression of aromatase gene isoforms, StAR, CYP11β and 3β-HSD in fish liver and the subsequent modulation by an estrogen mimic (Mortensen and Arukwe 2007).…”
Section: Star and P450scc Expression In Non-steroidogenic Tissuessupporting
confidence: 49%
“…2). Gaining a better understanding of the regulation of E2 synthesis is reliant on studies on extragonadal metabolism of androgens and estrogens, and molecular characterization of multiple forms of 17␤-HSD in fish, although such reports [31,44,[49][50][51][52] have been restricted to date.…”
Section: E2mentioning
confidence: 99%
“…Multiple different mammalian 17␤-HSD have been cloned and characterized to date. Human 17␤-HSDs differ in nucleotide cofactor and substrate specificities, subcellular compartmentalization and tissue-specific expression patterns [1][2][3][4][5][6]. One of these enzymes, the type 8 17␤-HSD (HSD17B8, also known as ke6) was primarily characterized as a protein whose abnormal gene regulation predominantly expressed in the liver and pancreas and moderately present in the skeletal muscle and kidney [13].…”
Section: Introductionmentioning
confidence: 99%